Advances in metal graphitic nanocapsules for biomedicine. Issue 6 (15th March 2022) - Li, Shengkai; Yang, Yanxia; Wang, Shen; Gao, Yang; Song, Zhiling; Chen, Long; Chen, Zhuo
Abstract: Metal graphitic nanocapsules have the advantages of both graphitic and metal nanomaterials, showing great promise in biomedicine. On one hand, the chemically inert graphitic shells are able to protect the metal core from external environments, quench the fluorescence signal from the biological system, offer robust platform for targeted molecules or drugs loading, and act as stable Raman labels or internal standard molecule. On the other hand, the metal cores with different compositions, sizes, and morphologies show unique physicochemical properties, and further broaden their biomedical functions. In this review, we firstly introduce the preparation, classification, and properties of metal graphitic nanocapsules, then summarize the recent progress of their applications in biodetection, bioimaging, and therapy. Challenges and their development prospects in biomedicine are eventually discussed in detail. We expect the versatile metal graphitic nanocapsules will advance the development of future clinical biomedicine. Abstract : In this review, we summary the preparation, classification, and properties of versatile metal graphitic nanocapsules, and then introduce the recent progress of their applications in biodetection, bioimaging, and therapy in detail. In addition, challenges and their development prospects in biomedicine are also discussed. We expect the metal graphitic nanocapsules will advance the development of future clinical biomedicine.